Investigasi Kasus dan Identifikasi Faktor Risiko Kematian Babi di Kabupaten Manokwari - Pumoko, Florida R.A.; Santoso, Budi; Sambodo, Priyo (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
This study aims to determine the chronology of death, the spread of the disease, the causes of the disease and the risk factors that affect the disease that caused the death of hundreds of pigs in three districts in Manowari Regency, West Papua Province. The research was conducted in West Manokwari District, Prafi District and Tanah Rubuh District. The research was conducted using a survey method with interview techniques and field observations. The number of correspondents is 117 breeders. The data obtained were analyzed descriptively using a case study technique based on the results of investigations and laboratory tests. The average age of breeders are 34.27-42.9 years with farming experience of 2.67-11.47 years. Number of swines are 77-128 tails. The maintenance system is extensive except in the West Manokwari District, which is intensive. The main feed sources are household/food stall waste and garden produce. Almost all farmers do not understand about disease control. The death of pigs in the study area generally occurred suddenly without showing any clinical symptoms, starting with the animals looking weak, having convulsions, experiencing respiratory problems and then dying. The disease has spread in all pens or herds of pigs in the study area. Based on the results of the RT-PCR test, the dead pigs were diagnosed as infected with ASFV, except for Tanah Rubuh District. The risk factors for this outbreak are the pig management system, biosecurity, anthropogenic (human factors), animal and fomite.